2022
DOI: 10.1016/j.ridd.2022.104200
|View full text |Cite
|
Sign up to set email alerts
|

How parents of children with autism spectrum disorder experience the COVID-19 pandemic: Perspectives and insights on the new normal

Abstract: Background Considering the fact that family members necessarily spend more time together during the pandemic, this study aims to reveal the perceptions of parents with children who have autism spectrum disorder of the COVID-19 pandemic in Turkey and their experiences of the difficulties during the pandemic. Method A qualitative phenomenology design was used in the study. Seven mothers and one father gave their consent and participated in the study. Data were collected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 26 publications
(59 reference statements)
4
20
0
1
Order By: Relevance
“…Results of his study indicate that both positive and negative consequences can be observed in the psychosocial functioning of people with ASD during the pandemic. The ambiguous impact of lockdown has been confirmed by a number of studies in which individuals with ASD as well as their families indicate both positive effects related to the reduction of social demands and normalization of daily life, as well as a negative impact of the pandemic on their mental health [ 48 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 95%
“…Results of his study indicate that both positive and negative consequences can be observed in the psychosocial functioning of people with ASD during the pandemic. The ambiguous impact of lockdown has been confirmed by a number of studies in which individuals with ASD as well as their families indicate both positive effects related to the reduction of social demands and normalization of daily life, as well as a negative impact of the pandemic on their mental health [ 48 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 95%
“…They have a detrimental impact on children’s everyday lives and limit their achievements. Due to the increased effort in caring for autistic children and finding ways to cope with their behavioral challenges, parents should be familiar with the environmental impacts ( 23 , 24 ). Autistic children tend to have a dysfunctional sensory system; this sensory processing disorder is perceived as the biggest challenge to surmount ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…The limited hours children with ASD have at school or other formal learning institutions may not be able to support the learning and language development phases of children with ASD. The roles played by home and family members in supporting learning development among children with autism are further emphasized by Mendoza, McKeithan, and Griswold (2019) and Boskuz-Genc and Sani-Bozkurt (2022).…”
Section: Home As An Informal Learning Institution and The Roles Of Au...mentioning
confidence: 99%
“…Parents and family members became more prominent in playing their role as the sole instructors to ensure continuity in the children with ASD's learning development. Various research has been conducted to capture the experiences, challenges and strategies of parents and family members in facilitating learning development of the child with autism in the family (Boskuz-Genc & Sani-Bozkurt, 2022;Heyworth et al, 2021;Hill, Keville & Ludlow, 2021).…”
Section: Home As An Informal Learning Institution and The Roles Of Au...mentioning
confidence: 99%